OPTIMAL DIGITAL CONTROLLER SYNTHESIS FOR A SYSTEM INCLUDING FOURTH ORDER CONTROL OBJECT - A. G. Stryzhniou; H. V. Lednik (Informatika)
An electro-hydraulic system with a fourth-order astatic control object containing lag and oscillatory elements is considered. The results of mathematical modeling of an optimal digital controller for this system are presented.Analytical expressions for digital controller transfer function coefficients via control object parameters and time step are obtained. System performance is verified by mathematical simulation.